Impact of a self-defense and self-assertion course on self-confidence and self-assurance of adult women - Elena Pocecco; Carina S. Bichler (Bern Open Publishing, 2024)
Introduction & Purpose The World Health Organization (WHO) defines violence as "the intentional use of physical force or power, threatened or actual, against oneself, another person or against a group or community, that either results in or has a high likelihood of resulting in injury, death, psychological harm, maldevelopment or deprivation" (World Health Organization, 2002, p. 5). There are different types of violence: physical, somatic or bodily violence, psychological, psychic or emotional violence, sexual violence, and violence involving deprivation or neglect (World Health Organization, 2002). The number of violent crimes across Austria rose by 16.9% in 2022 compared to the previous year, to 78,836 reports (Bundesministerium für Inneres, 2023). According to Statista (2024), Austria ranked sixth out of a total of 27 European countries in terms of the relative number of people affected by rape in 2021, with women affected 9.2 times more frequently than men (37.8 vs. 4.1 per 100,000 inhabitants, respectively). Austria ranked the same across Europe (out of 28 countries) with regard to the rate of female victims of intentional homicide, with a total of 0.98 homicides per 100,000 inhabitants (Europäisches Institut für Gleichstellungsfragen, 2022). Robust psychological differences between women and men, so-called gender gaps, have been shown in literature. One gender gap, which has been systematically researched since the 1990s and which can still be found across cultures, is the lower self-esteem and self-confidence of girls and women compared to boys and men (Casale, 2020). This gender gap can in turn lead to inequalities in social status and salary (Righetti et al., 2020). Psychological characteristics again appear to play an important role in violence. Indeed, Fazzone et al. (2000) identified personal protective factors, which include characteristics such as self-confidence, self-reliance, self-motivation, flexibility, and self-assurance, against community and interpersonal violence in home health care. Scientific studies have shown the effectiveness of self-defense courses on psychological characteristics such as self-confidence and assertiveness of participants (Brecklin, 2008; Gidycz & Dardis, 2014). In particular, most of the self-defense training programs that were analyzed showed positive changes in the measured psychological characteristics, although these results were not always consistent (Brecklin, 2008). In addition, supposed important characteristics such as self-confidence and self-assurance were not measured in the majority of cases (Brecklin, 2008). It is also worth mentioning that these older studies are mostly unpublished dissertations and, in accordance with Brecklin (2008), measures used should be revised to better fit the specific situational goals of self-defense training. This means that rather than just measuring assertiveness in everyday situations, it would be interesting to measure the likelihood of participants using assertiveness techniques in potential assault situations (Brecklin, 2008). The aim of the present study was therefore to investigate possible effects of a self-defense and self-assertion course (SSC) on self-confidence and self-assurance of adult women when being put into potential assault situations. Methods A quasi-experimental study was conducted with voluntary adult female participants in a two-day SSC lasting a total of 10 hours, along with adult female controls who also took part in the study. Inclusion criteria were female gender, age ≥ 18 years, fluency in German (reading and writing), and written informed consent. Participants who had taken part in a SSC or had been practicing martial arts/ combat sports within the 3 months before or during the surveyed period were excluded from the study. The participants were asked about the effects of the SSC as well as the control period using a standardized online questionnaire that complies with the ethical standards of the Department of Sports Science at the University of Innsbruck (certificate of good standing, 25/2006). The survey was conducted at two different times: directly before the start and directly after the end of the SSC (or before and after the simultaneous control period). The questionnaire in German language, which was developed based on relevant literature (Brecklin, 2008; Kidder et al., 1983), included both quantitative and qualitative variables such as open questions. Among other things, the participants were asked to imagine themselves in situations in which they were exposed to different forms as well as intensities of violence and to indicate their level of self-confidence and self-assurance in these situations. A visual analogue scale ranging continuously from 0 (does not apply at all) to 100 (applies completely) was used for this purpose. The SSC took place in the city of Innsbruck (Austria) at various educational institutions between May 2019 and February 2020. The program of the SSC was standardized and included physical defense techniques such as punching, pushing, and kicking techniques (~15%), protective postures, and liberation techniques (~50%), as well as theoretical inputs, exercises for setting boundaries, case studies, and role plays (~35%). Participants of the control group were free in choosing their activities during the control period, however, the participation neither in a SSC nor in martial arts/ combat sports was allowed. Data are presented as means ± standard deviations. After checking for normal distribution (Shapiro-Wilk test) and for homogeneity (Levene-Test), t-tests for independent samples were applied to check for differences between means of the change score of the assessed parameters of the two samples. P values < 0.05 were considered statistically significant. Results A total of 29 women took part in the study: 18 in the intervention group (IG, 40.0 ± 12.4 years) and 11 in the control group (CG, 30.5 ± 9.9 years). The age difference between the groups was not significant. The results indicate that women in the IG showed significant changes in several parameters compared to those in the CG, particularly when being put into situations in which they were exposed to different forms and intensities of violence. Accordingly, higher self-confidence and self-assurance were evident in the case of severe physical violence as well as in the case of mild psychological violence and higher self-assurance was shown in the case of severe psychological violence (Figure 1). There were no significant differences between the groups with regard to mild physical violence or mild and severe sexual violence. Furthermore, the assessment of the open questions with regard to the organization of the SSC and the program offered suggests that the courses were very well received by the participants. Discussion The study shows that a relatively short SSC leads to a higher increase of both self-confidence and self-assurance of adult women, both in situations of physical and psychological violence, compared to the control group. No significant differences between the groups were found with regard to situations of sexual violence, which is presumably due to the framework conditions of the courses (with only female participants). Therefore, future studies evaluating the impact of SSC on self-confidence and self-assurance of women exposed to sexual violence should include practice with male training partners. Additionally, in the interest of sustainability, it is important to achieve long-term changes in attitudes and behavior, which should be the goal of future research. The study's limitations that should be considered include the lack of an a priori power analysis, the absence of random group allocation, the missing standardization and supervision of the activity of the control group, the use of non-validated single-item scales, possible bias due to the overestimation of effects because of the temporal proximity of the survey to the SSC, and the failure to account for confounding variables such as age, which however did not differ significantly between groups. Conclusion Since violence is often perpetrated against women, particularly in Austria, and since women show less self-confidence and self-assurance than men, the promotion of high-quality SSC lasting at least 10 hours can be recommended to women in order to strengthen these resources.